2003
DOI: 10.1108/02686900310474299
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance, credit risk and legal reasoning – the case of Encompass Services Inc.

Abstract: Corporate accountability and quality of corporate disclosure have impacted on many companies and banks, particularly those grown through mergers and acquisitions (M&A) and companies have had to restate their financial statements. The growth of service and technology companies (particularly by M&A) presents numerous public policy, legal, regulatory and accounting issues. Some of these companies have substantial intangible assets and the accounting for M&A and investments can be manipulated to affect reported as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Eleventh , with regards to Spatio‐temporal Anti‐Compliance Coordination (SACC), it was found that there were similar patterns of non‐compliance (anti‐conformists) and managerial‐behaviour among the companies studied in [11, 56–59, 107] and [108]; which completely contradict the theories in [4, 5]. ▄…”
Section: Why the Hipster Effect Is Invalidmentioning
confidence: 98%
“…Eleventh , with regards to Spatio‐temporal Anti‐Compliance Coordination (SACC), it was found that there were similar patterns of non‐compliance (anti‐conformists) and managerial‐behaviour among the companies studied in [11, 56–59, 107] and [108]; which completely contradict the theories in [4, 5]. ▄…”
Section: Why the Hipster Effect Is Invalidmentioning
confidence: 98%